Perlindungan Hak Pihak Ketiga dalam Perkara Perdata Elektronik: Analisis Terhadap Potensi Abuse of Process (Menelaah Potensi Pelanggaran Hak Akibat Efesiensi Prosedural Digital) - Alisya Putri Santoso; Sidi Ahyar Wiraguna (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The digital transformation of civil litigation through e-court and e-litigation systems has significantly improved efficiency and accessibility within Indonesia’s judiciary. However, this procedural acceleration also presents new challenges, particularly regarding the protection of third-party rights that may be affected despite not being primary litigants. Using a normative juridical method supported by conceptual and comparative approaches, this study examines the extent to which the current system accommodates third-party interests and identifies potential abuse of process arising from digital efficiencies. The findings indicate that although third-party intervention mechanisms are formally recognized under the HIR and RBg, their implementation within electronic proceedings remains limited due to technical barriers, unequal access to information, and risks of procedural or evidentiary manipulation. These issues highlight the need to strengthen technical regulations, enhance transparency of digital documents, and enforce stricter verification of electronic notifications and evidence integrity. Such improvements are essential to ensure that judicial digitalization not only accelerates procedures but also upholds substantive justice for all interested parties, including third parties.